Kepemimpinan Kepala Sekolah dalam Upaya Meningkatkan Sumber Daya Manusia di Madrasah Aliyah Darussalam Tanjunganom Nganjuk - Rohmah, Fiki Nailatul; Chotimah, Chusnul (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The aim of this research is to describe the leadership role of principals in enhancing human resources despite facing challenges such as limited budget, and inadequate availability of resources. This study adopts a qualitative descriptive approach and involves school principals and deputy heads of the curriculum as research subjects. The data collection techniques employed include interviews, observations, and documentation. Through data analysis, this study presents an account of the principal's leadership efforts in improving human resources, identifies the challenges faced in this process, and proposes solutions to overcome them. These solutions encompass enhancing coordination among different work units, optimizing the utilization of existing resources, and fostering communication and collaboration among principals, teachers, and staff members. Furthermore, it is recommended that higher authorities provide increased support by allocating sufficient budgets and resources to enhance human resources in schools. The research concludes that effective leadership from school principals is crucial for improving human resources in educational institutions. The efforts made by principals, such as organizing workshops, training, and providing reinforcement and rewards, have the potential to contribute to human resource development.